Synergistic Effects of Chinese Herbal Medicine: A Comprehensive Review of Methodology and Current Research - Zhou, Xian; Seto, Sai Wang; Chang, Dennis; Kiat, Hosen; Razmovski-Naumovski, Valentina; Chan, Kelvin; Bensoussan, Alan (Frontiers in Pharmacology, 2016)
Traditional Chinese medicine is an important part of primary health care in Asian countries that has utilised complex herbal formulations (consisting 2 or more medicinal herbs) for treating diseases over thousands of years. There seems to be a general assumption that the synergistic therapeutic effects of Chinese herbal medicine derive from the complex interactions between the multiple bioactive components within the herbs and/or herbal formulations. However, evidence to support these synergistic effects remains weak and controversial due to several reasons, including the very complex nature of Chinese herbal medicine, misconceptions about synergy, methodological challenges to study design. In this review, we clarify the definition of synergy, identify common errors in synergy research and describe current methodological approaches to test for synergistic interaction. We discuss the strengthen and weakness of these models in the context of Chinese herbal medicine and summarise the current status of synergy research in CHM. Despite the availability of some scientific data to support the synergistic effects of multi-herbal and/or herb-drug combinations, the level of evidence remains low and the clinical relevancy of most of these findings is undetermined. There remain significant challenges in the development of suitable methods for synergistic studies of complex herbal combinations.